2022
DOI: 10.14309/ajg.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of Hepatitis C Virus Cryoglobulinemic Vasculitis After Sustained Viral Response After Interferon-Free Direct-Acting Antivirals

Abstract: INTRODUCTION:Direct-acting antiviral agents (DAAs) have modified the management of chronic hepatitis C virus (HCV) infection, including HCV-related cryoglobulinemic vasculitis (CryoVas). However, patients might experience vasculitis relapse, and no reliable predictors of CryoVas relapse after sustained virologic response (SVR) have been established. We aimed to describe HCV-CryoVas relapse rates and factors associated with it.METHODS:An international multicenter cohort where patients with HCV-CryoVas from Egyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(50 reference statements)
1
11
1
Order By: Relevance
“…The strongest evidence for the dependence of these lymphoproliferative disorders on stimulation by HCV comes from the fact that the cure of infection with direct-acting antivirals (DAAs) leads in most patients to clinical improvement ( 6 , 7 ). Nevertheless, cryoglobulins remain detectable in a substantial proportion of HCV-cured patients ( 6 ) and relapse of vasculitis occurs in about 12% of them ( 8 ), even many years after the clearance of virus and often in association with events characterized by increased production of immune complexes (ICs) such as infections or solid tumors ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence for the dependence of these lymphoproliferative disorders on stimulation by HCV comes from the fact that the cure of infection with direct-acting antivirals (DAAs) leads in most patients to clinical improvement ( 6 , 7 ). Nevertheless, cryoglobulins remain detectable in a substantial proportion of HCV-cured patients ( 6 ) and relapse of vasculitis occurs in about 12% of them ( 8 ), even many years after the clearance of virus and often in association with events characterized by increased production of immune complexes (ICs) such as infections or solid tumors ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, large clones of pathogenic B cells persist in the blood of many MC patients long after the clearance of HCV infection by antiviral therapy ( 16 ), and probably underlie the HCV-independent relapses of vasculitis observed in a significant proportion of patients ( 8 , 9 ). The pathogenic clonal B cells persisting after antiviral therapy progressively recover from some of their abnormal features, including BCR signaling defects, proneness to apoptosis and CD21 low phenotype, but remain impaired in their capacity to proliferate in response to TLR9 activation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, IgG type I CG patients had significantly higher mortality rate as compared to IgM isotype. These data shed light on IgG isotype and kidney involvement as independent poor prognostic factors in type I CG.There is a paucity of data regarding type I CG response to treatment, but response rates seem lower than those observed in type II and III CG [16][17][18]. Zhang et al described type I CG complete remission in 10/29 patients (34.5%),7 whereas Terrier et al reported complete remission achievement in 15/64 patients (23.4%) 5.…”
mentioning
confidence: 84%
“…Peripheral neuropathy was present in 81.7% of relapsing patients. Independent baseline risk factors associated with cryoglobulinemic vasculitis relapse were male sex, skin ulcers, kidney involvement at baseline, and peripheral neuropathy at the end of the DAA treatment [ 69 ]. A systematic review by Danishwar et al, which included data from 19 studies on persistence and recurrence of CV after the HCV cure with DAAs, reported a complete clinical response in 63.7% to 90.2% of DAA-treated patients.…”
Section: Impact On Extrahepatic Manifestationsmentioning
confidence: 99%